Erlotinib is effective against FLT3‐ITD mutant AML and helps to overcome intratumoral heterogeneity via targeting FLT3 and Lyn. Issue 8 (15th June 2020) - Cao, Zhi‐Xing; Guo, Chuan‐Jie; Song, Xiaominting; He, Jun‐Lin; Tan, Lu; Yu, Si; Zhang, Ruo‐Qi; Peng, Fu; Peng, Cheng; Li, Yu‐Zhi
Abstract: Erlotinib has potential therapeutic effect on acute myeloid leukemia (AML) in patients, but the mechanism is not clear. Effective tumor biomarkers for erlotinib in the treatment of AML remain poorly defined. Here, we demonstrate that erlotinib in vitro significantly inhibits the growth of the FLT3‐ITD mutant AML cell MV4‐11 and Ba/F3‐FLT3‐ITD cell via targeting FLT3, a certified valid target for the effective treatment of AML. In vivo, oral administration of erlotinib at 100 mg/kg/day induced rapid MV4‐11 tumor regression and significantly prolonged the survival time of bone marrow engraftment AML mice via inhibiting the FLT3 signal. Thus, the therapeutic benefits of erlotinib on AML are due to its ability to target FLT3. FLT3‐ITD mutation is an effective biomarker for erlotinib during AML treatment. In addition, we also demonstrate that erlotinib inhibits the activity of AML cell KG‐1 (no FLT3 expression) by targeting Lyn. Recently, single cell analysis demonstrated that intratumoral heterogeneity are one of the contributors in the relapse and FLT3 inhibitor resistance. Erlotinib could effectively inhibit the MV4‐11 cells via targeting FLT3, and inhibit KG‐1 cells via targeting Lyn. Therefore, Erlotinib also has the potential to overcome intratumoral heterogeneity via targeting FLT3 and Lyn.